Intranasal vaccination with ebola virus GP amino acids 258–601 protects mice against lethal challenge. Issue 41 (1st October 2018) - Su, Qiu-dong; He, Shi-hua; Yi, Yao; Qiu, Feng; Lu, Xue-xin; Jia, Zhi-yuan; Meng, Qing-ling; Fan, Xue-ting; Tian, Rui-guang; Audet, Jonathan; Qiu, Xiang-guo; Bi, Sheng-li
Highlights: The extracellular domain of the EBOV GP (N20) was prepared by prokaryotic expression and chromatography purification. CTA1-DD adjuvanted N20 vaccine could stimulate the humoral, mucosal and Th1 cellular immunity in mice. The vaccine could protect the mice against lethal challenges with the little morbidity. Abstract: Ebola virus (EBOV) disease (EVD) leads to lethal hemorrhagic fever with a case fatality rate as high as 90%, thus posing a serious global public health concern. However, while several vaccines based on the EBOV glycoprotein have been confirmed to be effective in animal experiments, no licensed vaccines or effective treatments have been approved since the first outbreak was reported in 1976. In this study, we prepared the extracellular domain of the EBOV GP protein (designated as N20) by prokaryotic expression and purification via chromatography. Using CTA1-DD (designated as H45) as a mucosal adjuvant, we evaluated the immunogenicity of N20 by intranasal administration and the associated protective efficacy against mouse-adapted EBOV challenge in mice. We found that intranasal vaccination with H45-adjuvanted N20 could stimulate humoral immunity, as supported by GP-specific IgG titers; Th1 cellular immunity, based on IgG subclasses and IFN-γ/IL-4 secreting cells; and mucosal immunity, based on the presence of anti-EBOV IgA in vaginal lavages. We also confirmed that the vaccine could completely protect mice against a lethal mouse-adapted EBOV (MA-EBOV) challenge with few side effects (based on weight loss). In comparison, mice that received N20 or H45 alone succumbed to lethal MA-EBOV challenge. Therefore, mucosal vaccination with H45-adjuvanted N20 represents a potential vaccine candidate for the prevention of EBOV in an effective, safe, and convenient manner.